Utilization of Polymer Composite for Development of Sustainable Construction Material - Ashmita Rupal; Sivansankara Rao Meda; Abhishek Gupta; Ishan Tank; Ashish Kapoor; Sanjay Kumar Sharma; T. Sathish; P. Murugan (Advances in Materials Science and Engineering)
Polymers have gained an extensive application due to their versatility of properties and benefits. Hence, the polymer blends and composites reinforced with different infusions at different scales, macro to nanofillers, can be fabricated, leading to specific tailormade applications. The main objective of this investigation is to overview the various studies carried out to reuse the waste materials like electroplating sludge, fly ash, etc. For the development of construction materials. This paper summarizes the use of polymers in composite material formulations for the development of building materials such as lightweight concrete, protective coatings, paver blocks, bricks, and structural components. Different tests, namely viscosity, density, flash point, amine value, and epoxy equivalent weight, were performed on polymers to find their suitability as binder materials. Various laboratory tests such as compressive strength, water absorption, tear resistance, flexural strength, and split tensile tests were carried out to determine the mechanical properties of the developed materials. By using polymers with the addition of sustainable filler and waste materials, the replacement of costly raw material can be achieved by more than 50% in the case of paver blocks, up to 60% in bitumen-polymer composite, 80% in case of lightweight concrete and polymer-based panels. This insight gives the framework for the selection of different materials, optimization of combining ratio of materials, and their testing for the development of polymer-based materials.